A Phenylbutenoid Dimer, cis-3-(3′, 4′-Dimethoxyphenyl)-4-[(E)-3′′′, 4′′′-Dimethoxystyryl] Cyclohex-1-ene, Exhibits Apoptogenic Properties in T-Acute Lymphoblastic Leukemia Cells via Induction of p53-Independent Mitochondrial Signalling Pathway. (28th February 2013) - Anasamy, Theebaa; Abdul, Ahmad Bustamam; Sukari, Mohd Aspollah; Abdelwahab, Siddig Ibrahim; Mohan, Syam; Kamalidehghan, Behnam; Azid, Mohd Zulkhairi; Muhammad Nadzri, Nabilah; Andas, A. Reenaa Joys; Kuan Beng, Ng; Hadi, A. Hamid A.; Sulaiman Rahman, Heshu
Abstract : The current study was designed to evaluate the in vitro cytotoxicity effect of a phenylbutenoid dimer, cis -3-(3′, 4′-dimethoxyphenyl)-4-[( E )-3 ‴, 4 ‴ -dimethoxystyryl]cyclohex-1-ene (ZC-B11) isolated from the rhizome of Zingiber cassumunar on various cancer cell line, and normal human blood mononuclear cells, and to further investigate the involvement of apoptosis-related proteins that leads, to the probable pathway in which apoptosis is triggered. Cytotoxicity test using MTT assay showed selective inhibition of ZC-B11 towards T-acute lymphoblastic leukemia cells, CEMss, with an IC50 value of 7.11 ± 0.240 μ g/mL, which did not reveal cytotoxic effects towards normal human blood mononuclear cells (IC50 > 50 μ g/mL). Morphology assessments demonstrated distinctive morphological changes corresponding to a typical apoptosis. ZC-B11 also arrested cell cycle progression at S phase and causes DNA fragmentation in CEMss cells. Decline of mitochondrial membrane potential was also determined qualitatively. In the apoptosis-related protein determination, ZC-B11 was found to significantly upregulate Bax, caspase 3/7, caspase 9, cytochrome c, and SMAC and downregulate Bcl-2, HSP70, and XIAP, but did not affect caspase 8, p53, and BID. These results demonstrated for the first time the apoptogenic property of ZC-B11 on CEMss cell line, leading to the programmed cell death via intrinsic mitochondrial pathway of apoptosis induction.